The experience of puberty in Iranian adolescent girls: a qualitative content analysis - Golchin Nayereh Azam; Hamzehgardeshi Zeinab; Fakhri Moloud; Hamzehgardeshi Leila (BMC, 2012)
Abstract Background Adolescence is an important stage in human life span. Physiologic changes associated with puberty manifest themselves in often complex and bizarre ways to which girls show different reactions. This study aims to explore to puberty experiences in adolescent girls who live in the city of Sari in Iran. Methods The present study is a qualitative study of content analysis. Sampling took place in the city of Sari, Iran and was objective focused in accordance with qualitative studies. Participants were 38 girls of 12-20 years old who had at least experienced 3 menstrual cycles. Data was collected by means of focus group and in-depth interviews. Results As follows, Seven main themes were extracted from the interviews are follows: Menarche as the most unpleasant event in puberty, getting nervous about and ashamed of bodily changes, psychological changes, discordance with parents, sexual orientation and the need for education on this issue, scholastic dysfunction and religious considerations. Conclusion The results showed that for the majority of the participants puberty was an unpleasant experience. Most of them were in need of education on how to go about the issues surrounding puberty. The society, families and of course the adolescents themselves are responsible to work together in order to create an atmosphere in which correct information on puberty and the associated issues are readily accessible.